Developing and training mental toughness in sport: a systematic review and meta-analysis of observational studies and pre-test and post-test experiments. Issue 1 (16th June 2020) - Stamatis, Andreas; Grandjean, Peter; Morgan, Grant; Padgett, Robert Noah; Cowden, Richard; Koutakis, Panagiotis
Abstract : Objective: To investigate the efficacy of interventions designed to train and develop mental toughness (MT) in sport. Design: Systematic review and meta-analysis. Data sources: Journal articles, conference papers and doctoral theses indexed in Embase, Scopus, PubMed and SPORTDiscus from inception to 22 November 2019. Eligibility criteria for selecting studies: Observational and pre–post experimental designs on the efficacy of physical and/or psychological interventions designed to promote MT in athletes. Results: A total of 12 studies, published between 2005 and 2019, were included in the review. A majority of the studies included a sample comprised exclusively of male athletes (54.55%), MT interventions were primarily psychological (83.33%) and most studies measured MT via self-report (75%). The Psychological Performance Inventory (25%), the Mental Toughness Questionnaire-48 (16.67%), and the Mental, Emotional and Bodily Toughness Inventory (16.67%) were the most popular inventories used to measure MT. Methodological quality assessments for controlled intervention studies ( k =7), single group pre-test–post-test designs ( k =4) and single-subject designs ( k =1) indicated that the risk of bias was high in most (75%) of the studies. The meta-analysis involving k =10 studies revealed a large effect ( d =0.80, 95% CI 0.30 to 1.28), with variability across studies estimated at 0.56. Conclusion: Although the findings of this review suggest there are effective, empirically based interventions designed to train MT in sport, practitioners should be aware of the level of validity of intervention research before adopting any of the MT training programmes reported in the applied sport psychology literature.